Chemical stabilization of Cd-contaminated soil using biochar. (January 2018) - Van Poucke, R.; Ainsworth, J.; Maeseele, M.; Ok, Y.S.; Meers, E.; Tack, F.M.G.
Abstract: Metal smelter activities have contaminated approximately 700 km 2 of the Campine region in Belgium and The Netherlands. This work aimed to assess the effectiveness of biochar added to this soil using compost, peat or lime as a reference. Amendments were mixed with the contaminated soil at a 2 or 4% ratio (w:w) and equilibrated for up to 44 weeks. Treatment with biochar released significantly lower concentrations of Cd in the soil solution than compost or peat. In comparison to the blanks, soil solution concentrations of Cd were reduced 67% on average for the 4% biochar treatment and increased 30% and 231% for the 4% compost and 4% peat treatments, respectively. The lime treatment was equally effective as the biochar in reducing Cd concentrations. Similar trends were observed when conducting consecutive CaCl2 extractions. However, pH-stat leaching tests showed biochar and the other organic amendments to be more effective than lime in retaining Cd from the solution. The combined effect of pH and metal complexation capacity of added biochar resulted in an effective reduction in soluble Cd concentrations that lasted longer than when lime, compost or peat are used. Highlights: Biochar and lime increased soil pH the most and reduced the Cd availability. After soil acidification events, organic amendments reduced the available Cd. Biochar combines the pH effect of lime with a high sorption capacity.